Distribution, sources, and air–soil exchange of OCPs, PCBs and PAHs in urban soils of Nepal. (June 2018) - Pokhrel, Balram; Gong, Ping; Wang, Xiaoping; Chen, Mengke; Wang, Chuanfei; Gao, Shaopeng
Abstract: Due to the high temperature and extensive use of organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAHs), tropical cities could act as secondary sources of these pollutants and therefore received global concern. As compared with other tropical cities, studies on the air–soil exchange of OCPs, PCBs and PAHs in tropical Nepali cities remained limited. In the present study, 39 soil samples from Kathmandu (capital of Nepal) and 21 soil samples from Pokhara (second largest city in Nepal) were collected The soil concentrations of the sum of endosulfans ( α - and β -endosulfans) ranged from 0.01 to 16.4 ng/g dw. Meanwhile, ∑dichlorodiphenyltrichloroethane (DDTs) ranged from 0.01 to 6.5 ng/g dw; ∑6PCBs from 0.01 to 9.7 ng/g dw; and ∑15PAHs from 17.1 to 6219 ng/g dw. High concentrations of OCPs were found in the soil of commercial land, while, high soil PAH concentrations were found on tourist/religious and commercial land. Combined the published air concentrations, and the soil data of this study, the directions and fluxes of air–soil exchange were estimated using a fugacity model. It is clear that Nepal is a country contributing prominently to secondary emissions of endosulfans, hexachlorobenzene (HCB), and low molecular weight (LMW) PCBs and PAHs. The flux for all the pollutants in Kathmandu, with ∑endosulfans up to 3553; HCB up to 5263; and ∑LMW-PAHs up to 24378 ng m −2 h −1, were higher than those in Pokhara. These high flux values indicated the high strength of Nepali soils to act as a source. Graphical abstract: Highlights: Past use of endosulfans and current use of DDTs were found. High concentrations of OCPs were found in the soil of commercial land. High soil PAH concentrations were found on tourist/religious and commercial land. Nepali urban soil is acting as a "secondary source" for endosulfans and HCB.